DINAMIKA DEPRESI PADA PENDERITA AIDS - Imadduddin Parhani (Jurnal Studia Insania, 2016)
Depression is a major mental health problem today. This is very important because people with depression productivity will decrease and this is very bad for a society and a country that is building. There are at least four chronic diseases that allow the depression sufferer, one of which is HIV and AIDS. Given the uncertainty over the fate of people living with HIV and AIDS had the potential to give rise to feelings of anxiety and depression. Someone who is infected with HIV and AIDS will be overcome by a feeling of dying, guilt about the behavior that makes infection, and taste sequestered by others.The cause of depression in people with HIV and AIDS by cognitive approach that is the mindset of people who deviate from the pattern of the logical interpretation or misinterprets an event or events, focusing on the negative situations that happened to him, and hope that pessimistic and negative about the future. Symptoms are raised is their depressed mood, decreased interest or pleasure in absolute terms, average of worthlessness or excessive guilt, thoughts of death. Response or reaction that occurs is refused, angry, and depressed when he learned he was infected with HIV and AIDS, and eventually be able to accept his situation. Efforts are being made to reduce depression are manifold. One is through social support to colleagues who also have HIV and AIDS.